Chariotry and prone burials: reassessing late Shang China's relationship with its northern neighbours - Rawson, J; Chugunov, K; Grebnev, Y; Huan, L (Springer, 2020)
In place of the traditional view that raids and invasion from the north introduced new weapons and chariots to the Shang (c. 1200 BC), we argue that archaeological evidence illustrates the presence of several regional groups at or near the late Shang centre, Anyang. Here we review burial practices at Anyang dating to the late second millennium BC, and describe a substantial group of prone burials that reflect a ritual practice contrasting with that of the predominant Shang elite. Such burials occur at all social levels, from victims of sacrifice to death attendants, and include members of lower and higher elites. Particularly conspicuous are chariot drivers in some chariot pits. An elite-level link with chariots is confirmed by the burial of a military leader in tomb M54 at Huayuanzhuang at Anyang, with tools that match exactly those of chariot drivers. Given that prone burial is known to the north, in the Mongolian region that provided chariots and horses to the Shang, a route can be traced eastwards and southwards, down the Yellow River, and then through mountain basins to Anyang. Our inference is that a group originally from outside the Central Plains can be identified in these distinctive burials. This marks a first step towards understanding the heterogeneity in the central population of the late Shang.